2021
DOI: 10.1016/j.jbc.2021.100465
|View full text |Cite
|
Sign up to set email alerts
|

TNF receptor-associated factor 3 restrains B-cell receptor signaling in normal and malignant B cells

Abstract: TRAF3 has diverse signaling functions, which vary by cell type. Uniquely in B lymphocytes, TRAF3 inhibits homeostatic survival. Highlighting the role of TRAF3 as a tumor suppressor, loss-of-function TRAF3 mutations are associated with human B-cell malignancies, while B-cell-specific deletion of TRAF3 in mice leads to autoimmunity and lymphoma development. The role of TRAF3 in inhibiting noncanonical NF-κB activation, CD40 and BAFF-R signaling to B cells is well documented. In contrast, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…TRAF3 inhibits IL-2R signaling in T cells, promoting Treg differentiation ( 42 ), and suppresses signaling mediated by the IL-6R and the B cell antigen receptor in B cells ( 43 , 68 ). Signaling through IL-2 and IL-6 receptors is tightly regulated by TRAF3 recruited phosphatases, PTPN2 and PTPN22, respectively ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRAF3 inhibits IL-2R signaling in T cells, promoting Treg differentiation ( 42 ), and suppresses signaling mediated by the IL-6R and the B cell antigen receptor in B cells ( 43 , 68 ). Signaling through IL-2 and IL-6 receptors is tightly regulated by TRAF3 recruited phosphatases, PTPN2 and PTPN22, respectively ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…TRAF3 inhibits IL-2R signaling in T cells, promoting Treg differentiation (42), and suppresses signaling mediated by the IL-6R and the B cell antigen receptor in B cells (43,69).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, in vitro inhibition by ibrutinib resulted in reduced pSyk, even in Btk −/ − B cells [ 45 ], indicating an off‐target effect of ibrutinib. Very recently, BCR rewiring was also reported in a mouse model with B‐cell specific deletion of TNF receptor associated factor 3 (TRAF3); TRAF3‐deficient B cells showed increased BCR responsiveness in upstream signaling molecules, enhanced calcium influx, and pErk signaling upon BCR stimulation [ 46 ]. This is similar to our findings, although we did not observe increased calcium signaling.…”
Section: Discussionmentioning
confidence: 99%
“…B cells were derived from the pluripotent stem cells of bone marrow, which could proliferate and differentiate into a large number of plasma cells when stimulated by antigens. Plasma cells could synthesize and secrete antibodies in the blood circulation, which plays an important role in the development and regulation of the immune system (Whillock et al, 2021). The results indicated that when the final mass concentration of polysaccharide was 2.5-20 μg/ml, the proliferation effect of B cells was enhanced.…”
Section: Effect Of Ba-t and Pc-1 On Proliferation Of B Cellsmentioning
confidence: 99%